2018
DOI: 10.1016/j.ast.2018.04.026
|View full text |Cite
|
Sign up to set email alerts
|

Method for simulating the performance of a boundary layer ingesting propulsion system at design and off-design

Abstract: Boundary layer ingestion has emerged as a potential propulsion concept on novel aircraft configurations for the future. As these concepts progress, preliminary design tools are required that enable the simulation of these aircraft and the rapid analysis of multiple configurations. Simulation tools for boundary layer ingesting propulsion systems tend to focus on proving performance benefits at design point. However, the simulation of aircraft configurations that utilise boundary layer ingestion requires a metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…The fuel is to be stored at 21.5K and 1.25bar, so insulation will require a great deal of attention. The authors based the tank design philosophy on expanded analytical studies based on previous Cranfield work (16)(17)(18) . The tanks must be insulated to prevent heat leakage into the liquid hydrogen with no need for an active cooling system.…”
Section: Fuel Tank Integrationmentioning
confidence: 99%
“…The fuel is to be stored at 21.5K and 1.25bar, so insulation will require a great deal of attention. The authors based the tank design philosophy on expanded analytical studies based on previous Cranfield work (16)(17)(18) . The tanks must be insulated to prevent heat leakage into the liquid hydrogen with no need for an active cooling system.…”
Section: Fuel Tank Integrationmentioning
confidence: 99%
“…This condition can lead to differences in variables. Some of the calculated data are shown in Tables [18][19][20].…”
Section: High-altitude Cruisementioning
confidence: 99%
“…These models were applied to simplify the calculation while ensuring a certain degree of accuracy. Goldberg et al [18] developed a method to match propulsion system flow and tube flow to simulate the internal flow field under boundary layer inhalation and validated it with NASA's N3-X model. They found that the inlet distortion affected thrust more remarkably than fan efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Boundary layer ingestion has stood out as a solution to improve both aerodynamics and propulsion performance [1][2][3]. The aim of ingesting the boundary layer is to reenergize the slower air moving near the surface of the body to reduce the drag due to friction.…”
Section: Introductionmentioning
confidence: 99%